From migration flows to migration systems: the case of Ukraine - Pyatkovska, Oksana (Видавництво Львівської політехніки, 2013)
The author of the article singles out countriesparticipants of migration systems with Ukraine as a source country and, by ranking them according to the selected indicators, makes the analysis of the formation and effectiveness of migration systems. As the result, an attempt to predict possible destination countries of future migration outflows from Ukraine is made.
Keywords: migration flows; labor migration; migration systems; export-import of goods and cervices; foreign direct investments; remittances